Potential of Biocellulose Nanofibers Production from Agricultural Renewable Resources: Preliminary Study - Dahman, Y.; Jayasuriya, K.E.; Kalis, M.
In the present preliminary study, we report results for the biocellulose nanofibres production by Gluconacetobacter xylinus. Production was examined by utilizing different feedstocks of single sugars and sugar mixtures with compositions similar to the acid hydrolyzates of different agriculture residues. Profiles for cell proliferation, sugar consumption, and the subsequent pH changes were thoroughly analyzed. Highest biocellulose production of 5.65 g/L was achieved in fructose medium with total sugar consumption of 95.57
Keywords: BACTERIAL CELLULOSE; NANOFIBERS; FEEDSTOCK; AGRICULTURE RESIDUES; WHEAT STRAW; CORN FIBRE; DDGS